Sustainable synergy via clean energy technologies and efficiency dynamics - Yu Z.; Kamran H.W.; Amin A.; Ahmed B.; Peng S. (Elsevier Ltd, 2024)
The sustainability paradigm has gained global attention, and the same has been expected from the economies having increasing levels of environmental footprints over the past couple of decades. This research aims to investigate the nexus between clean energy technologies and climate change mitigation among the top ecologically pollutant (TEP) economies during 19962020. The research incorporated other drivers of climate change, including energy efficiency, industrialization, and sustainable policies through environmental regulations. The methodological context covers the necessary preliminary tests and the Method of Moment Quantile Regression (MMQR). The preliminary results indicate that TEP economies are interdependent with the heterogenous slope coefficients, stationarity data trends, and cointegrated relationships. The findings from the MMQR unveiled that clean energy technologies tend to mitigate climate change from 0.10th to 0.70th quantiles. Relatedly, energy efficiency reduces the environmental burden across all the quantiles except for the 0.10th one. Conversely, industrialization and economic growth cause an upward shift in climate change among TEP economies across all the quantiles, suggesting a need to shift production-based economies to more service-intensive ones. However, the study found no significant evidence for the nexus between sustainable environmental policies and climate change. The robustness checks also validate the MMQR estimations